Cardiocerebral resuscitation: advances in cardiac arrest resuscitation (Faculty of Medicine Universitas Indonesia, 2011)
Cardiac arrest remains a leading cause of death in the world. Although advances in emergency cardiac care has been achieved, the survival rate of those non hospitalized hospital cardiac arrest remains low. Update in guidelines for CPR and emergency cardiovascular, their approach to out of hospital cardiac arrest is far from optimal. This provides an opportunity to advocate cardiocerebral resuscitation as an alternative to traditional cardiopulmonary resuscitation for non hospitalized cardiac arrest. Because cardiocerebral resuscitation results in improved survival and cerebral function in patients with witnessed cardiac arrest and a shockable rhythm whom have greatest chance of survival, it should replace CPR especially for non hospitalized cardiac arrest.(Med J Indones 2011; 20:306-9)